I will protect you : a true story of twins who survived Auschwitz - Kor, Eva Mozes; Davidson, Danica (Little, Brown and Company, 2022)
"A memoir of a young girl's childhood in wartime Romania, unlikely survival as a "Mengele twin" subjected to cruel Nazi medical experiments in Auschwitz, and postwar journey to forgiveness"--